PENGARUH PERSEPSI WAJIB PAJAK ATAS PENERAPAN E-SYSTEM DAN ACCOUNT REPRESENTATIVE TERHADAP KEPATUHAN (STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA KENDARI) - Ulyani, Thropy Atika (JURNAL AKUNTANSI, 2016)
Study research aims to examine the effect on taxpayer perceptions about implementation of e-System and Account Representative to tax compliance. Data used in this research are primary data collected from the results of questionnaires to the individual taxpayer in the Small Taxpayer Office Kendari. Sample in study researche was 50 questionnaire respondents eligible to be a source of data with accidental sampling. Data analysis in this research uses multiple linear regression analysis with SPSS 21.The result of this research using t test shows that the partial e-System has a significant level of 0,027. While Account Representative mempunyi significant level of 0.001. This shows that the partial each variable e-System and Account Representative significant effect on tax compliance. From the results of the F test shows that the significance level of 0.001, this shows E-System and Account Representative together with significant influence on tax compliance. Test showed the value of the coefficient of determination R Square of 0.468, indicating that the ability of the variables E-System and Account Representative to the taxpayer compliance is 46.8%, while the remaining 53.2% is explained by other variables not examined.Â Keywords: e-System, Account Representative, tax compliance.